INOVASI PRODUK SYARIAH - Danila, Nevi (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The growth of shariah banks has increased rapidly. At the same time, Indonesia financial market has developed shariah financial instruments. In order to keep up with this development, shariah banks need to innovate their productsÂ for being remain competitive domestically and abroad. On top of that, the shariah product innovation has to concern on risk management to minimize the exposure. This paper elaborates eight (8) model shariah business which include the hedging. The models are namely Value-Based Salam; Bai Bil Wafa (repurchase agreement) combination with Ijara with Option Stipulation; Bai Istijrar; Murabaha-Bilateral Mutual Adjustment; Credit-Based Mudarabah; Third Party Hedging;Â Musharakah-Deferred Sale with Partnership; Diminishing Partnership. Key words: Value-Based Salam; Bai Bil Wafa (repurchase agreement) with Option Stipulation; Bai Istijrar; Murabaha-Bilateral Mutual Adjustment; Credit-Based Mudarabah; Third Party Hedging;Â Musharakah-Deferred Sale with Partnership; Diminishing Partnership